Antarctic ice shelf pinning point change classification 1973-2022 ... - Miles, Bertie; Bingham, Rob (University of Edinburgh. School of GeoSciences, 2023)
Mass loss of the Antarctic Ice Sheet has been primarily driven by thinning of the floating ice shelves that fringe the ice sheet, reducing their buttressing potential and causing land ice to accelerate into the ocean. However, observations of ice-shelf thickness change by satellite altimetry only stretch back to 1992 and prior information about thinning remains unquantified. Here, we present a new way of assessing ice-shelf thickness change that focusses on changes to pinning points, local bathymetric highs on which ice shelves are anchored and which are typically expressed as surface protuberances on the ice-shelves' surfaces. We utilise the full Landsat archive to map the evolution of pinning points around the Antarctic coastline over 50 years, and thus by proxy infer changes to ice-shelf thickness back to 1973. Ice shelves in the Amundsen Sea sector and in Wilkes Land were already thinning from 1973-1989, meaning the processes driving mass loss in these key sectors of Antarctica have been ongoing for at ...